Evidence for asthenospheric flow rotation in northwest Canada: insights from shear wave splitting. Issue 3 (6th October 2021) - Bolton, Andrew R; Schutt, Derek L; Aster, Richard C; Audet, Pascal; Schaeffer, Andrew J; Estéve, Clément; Freymueller, Jeffrey T; Cubley, Joel F
SUMMARY: The Mackenzie Mountains (MM) of northwest Canada are an actively uplifting, seismogenic salient of the northern Canadian Cordillera that lie 750 km NE of the main Pacific–North America plate boundary. We present new shear wave splitting measurements from a linear array transecting the region to characterize upper-mantle anisotropy and the relative role of the lithosphere and asthenosphere in MM uplift. A gradual rotation in anisotropy occurs across the Canadian Cordillera, with stations nearest to the craton yielding NE fast-axis orientations that are subparallel to North America absolute plate motion (∼230°). Moving SW from the craton, across the MM and towards the plate boundary, fast-axis orientations rotate to become aligned with major lithospheric fabrics (NW–SE). Previous work has shown that the Cordilleran lithosphere is thin (≈50 km) in this region. We therefore interpret these results to primarily reflect sublithospheric flow. Three possibilities for asthenospheric flow are presented, but none of them fit the data well. Therefore, we believe that flow in the SW is due to upwelling from the slab window that opened up around 45–25 Ma, although it is possible the lithosphere is more than 50 km in thickness, in which case these splits reflect the tectonic fabric of the region.